Design and test a converging and de Laval nozzle using additive manufacturing - Chen, Mingtai; Baby , Ruksana; Dillard , Seth; Lee , Yi Tsung; Ekkad , Srinath (Frontiers in Aerospace Engineering, 2022)
The advent of additive manufacturing technology has facilitated the design and fabrication of parts and models in both academia and aerospace industry. Compressible flow in the nozzles is not a new research topic; however, the accuracy of the experimental results obtained from the nozzles using additive manufacturing has not been assessed comprehensively. Surface roughness and strength of 3D-printed nozzles are two major concerns when they are applied to compressible nozzle flows. In this paper, a converging and de Laval nozzle fabricated by additive manufacturing using ABS filament are designed and tested. In general, the experimental results compare well with the analytical solutions from isentropic equations for the converging nozzle and the numerical simulations conducted in ANASYS Fluent for the de Laval nozzle. 3D-printed nozzles can be employed to quickly demonstrate and verify novel ideas and concepts on the pedagogy and research at large Reynolds numbers.